INOVASI PENGOLAHAN BELIMBING DESA MOJO MELALUI KKN TEMATIK SEBAGAI UPAYA PEMULIHAN PEREKONOMIAN PASCA PANDEMI COVID 19 - Fetrika Anggraini; Ahmad Mansur; Yogi Prana Izza (Jurnal Abdi Insani, 2022)
The pandemic triggers an economic and agricultural recession. Efforts to recover from the economic crisis can improve processing, especially local wisdom products through KKN. The potential developed in Mojo village, Kalitidu sub-district, is a tourism village potential as a fruit center. However, problems arise when the harvest occurs. Starfruit is abundant, has a low price and has a short shelf life, it will rot. This is detrimental to farmers, so new innovations are needed so that starfruit can be enjoyed out of season such as processed jam. The purpose of this service is to restore the economy of Mojo village after the covid pandemic through processing starfruit jam. The problem solving method in this community service activity consists of several stages, namely observation, literature study and continued with training on making starfruit jam with local residents with 80 participants and followed by packaging training to completion. The result of this activity is an innovative product of processing star fruit into jam. In addition, training activities with residents become new knowledge so that it can be applied independently by Mojo villagers in entrepreneurship. With the creation of new products from processed star fruit, it is hoped that it can provide benefits to the community as new knowledge, and can increase the selling value of star fruit from the previous period.